“Prevalencia de parásitos gastrointestinales en porcinos de traspatio en la parroquia de Toacaso, cantón Latacunga en la provincia de Cotopaxi” - Cuenca Cuenca, Elvis Adrián (2023)
Gastrointestinal parasitosis is an important problem for both animal and public health. Therefore, the objective research was to determine gastrointestinal parasites prevalence in backyard pigs Toacaso parish, Latacunga canton in Cotopaxi province. It was developed through the use of qualitative methodology, by simple random probability sampling where 330 pigs were analyzed between males and females divided into groups of 110 animals by zones (high, medium and low zone) and considering three neighborhoods for each parish zone. Fecal samples were taken directly from the rectum by stimulating animals anal sphincter, analyzed in Technical University of Cotopaxi laboratory using Sheather Sugar flotation technique. In this way, polyparasitism cases were established, with eleven types of identified parasites. The middle zone presented a parasitic prevalence of 37.13%, with majority presence of coccidia (41.54%), oesophagostomum (27.96%) and hyostrongylus (24.86%). The high zone presented a parasitic prevalence of 33.64%, with the majority coccidia presence (33.09%), hyostrongylus (26.77 %) and oesophagostomum (18.25%). The lower zone presented a parasitic prevalence of 29.23%, with majority coccidia presence (51.85%), oesophagostomum (28.16%) and hyostrongylus (11.82%). Likewise, by means of chi-square analysis, it was determined that there was no relationship between the presence gastrointestinal parasites cases and variables age and sex. The prevalence of positive parasitosis cases varied from 0 to 12 months (97.67%), from 0 to 6 months (93.10%) and from 7 to 12 months (97.35%); and between sex of the pigs, where males presented 95% and females 95.3% of positive polyparasitism cases. With the elaboration of epidemiological map, the different levels of prevalence were represented by means of colors and different parasites types were georeferenced symbols, based on the number of eggs present in the neighborhoods and communities. Finally, a preventive deworming plan was proposed using Sulfonamides (Sulfamide), for their action in the control and eradication of coccidia, and Benzimidazoles (Albendazole, Febendazole), for their ovicidal, larvicidal and tenicidal action.